SINGLE PHOTON BONE DENSITOMETRY IN MULTIPLE MYELOMA - Bacovsky, Jaroslav; Scudla, Vlastimil; Pospisil, Zdenek (Biomedical papers, 1999)
The study was performed in 45 patients with multiple myeloma. There was found significant correlationbetween diminished bone mineral density of forearm and duration of the disease. No correlation between bonemineral density and biochemical markers of osteolysis (pyridinoline and deoxypyridinoline in urine) and serumlevels of cytokines was found.
Keywords: Multiple myeloma / Bone densitometry